2023
DOI: 10.1097/nna.0000000000001308
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Resiliency and Health in Practicing Nurses Before and During COVID-19

Lois M. Stallings Welden,
Chen Chen,
Kate Willegal-Russ
et al.

Abstract: OBJECTIVES The aim of this study was to compare the degree of resilience and self-perceived physical and mental health in nurses before and during the COVID-19 pandemic. BACKGROUND Work-related stress among nurses is recognized as an antecedent of burnout, which in turn impacts resiliency and well-being. The work of nursing has long been noted as stressful. Although nurse resilience and perceived well-being have been shown to decrease during a period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A recent quantitative study further supports how communication by nurse leaders is vital in dealing with the COVID-19 pandemic 35 . Another study highlighted the importance of communication in promoting resilience 22 . Previous studies involving healthcare response to the severe acute respiratory syndrome (SARS) outbreak illustrate similar themes such as the importance of flexibility and the search for up-to-date information 36 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent quantitative study further supports how communication by nurse leaders is vital in dealing with the COVID-19 pandemic 35 . Another study highlighted the importance of communication in promoting resilience 22 . Previous studies involving healthcare response to the severe acute respiratory syndrome (SARS) outbreak illustrate similar themes such as the importance of flexibility and the search for up-to-date information 36 …”
Section: Discussionmentioning
confidence: 89%
“…A nonexperimental-design study on the development and validation of authentic nurse leadership indicated that nurse leaders used altruism and caring to cope causing them to be less likely to advocate for themselves 21 . Another study among nurses during the pandemic revealed the need for nurse leaders to support clinical nurse resilience by adopting transformational leadership–style strategies such as encouraging nurses to care for themselves and providing a safe space for effective dialogue 22 …”
Section: Role Of Nurse Leadermentioning
confidence: 99%